Characterization and Phylogenetic Analysis of Ancient Italian Landraces of Pear - Ferradini, Nicoletta; Lancioni, Hovirag; Torricelli, Renzo; Russi, Luigi; Dalla Ragione, Isabella; Cardinali, Irene; Marconi, Gianpiero; Gramaccia, Mauro; Concezzi, Luciano; Achilli, Alessandro; Veronesi, Fabio; Albertini, Emidio (Frontiers in Plant Science, 2017)
Pear is one of the oldest fruit tree crops and the third most important temperate fruit species. Its domestication took place independently in the Far East (China) and in the Caucasus region. While the origin of Eastern Asian cultivars is clear, that of European cultivars is still in doubt. Italy has a wealth of local varieties and genetic resources safeguarded by several public and private collections to face the erosion caused by the introduction of improved varieties in specialized orchards. The objectives of the present study were: (i) to characterize the existing germplasm through nuclear (SSR) and (ii) to clarify the genetic divergence between local and cultivated populations through chloroplast DNA (cpDNA) markers in order to provide insights into phylogenetic relationships of Pyrus spp. For this reason, 95 entries from five different germplasm collections, including nine European, Mediterranean and Eastern Asian species, were analyzed, and the intergenic accD-psaI sequences were compared to the worldwide distributed dataset encompassing a total of 298 sequences from 26 different Pyrus species. The nine nuclear SSRs were able to identify a total of 179 alleles, with a loci polymorphism P=0.89. Most of the variation (97%) was found within groups. Five accessions from different sources were confirmed to be the same. Eight out of 20 accessions of unknown origin were identified, and six synonyms were detected. Locus NH030a was found to be monomorphic in all the cultivated accessions and in reference species interfertile with P. communis, leading to hypothesize selection pressures for adaptation to cultivation. The cpDNA sequences of the 95 accessions were represented by 14 haplotypes, six of which (derived from P. communis, P. cossonii and P. ussuriensis) are recorded here for the first time and may suggest the ancient origin of some local varieties. The network analysis of the 298 cpDNA sequences allowed two different haplogroups, Eastern and Western Eurasia, to be defined, supporting recent views of a clear division between Occidental and Oriental species. By combining the results from nuclear and uniparental markers, it was possible to better define many unknown accessions.